HOW TO CREATING THE SUSTAINABLE LONG-TERM CIVIL SERVICE PENSION FUNDING SYSTEM IN ASIAN COUNTRIES? - Theysa Sahlani Pratiwi; Viani Naufalia (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the authority of BMT in managing Islamic Social Finance (ISF) based on Indonesian regulations, specifically Law No. 23 of 2011 on Zakat Management and Law No. 41 of 2004 on Waqf. This qualitative research employs a juridical-normative approach and is categorized as field research. Primary data were obtained through field interviews, and data analysis was conducted descriptively. The findings reveal that although BMT has an organizational structure with a māl manager separating the management of baytūl māl and baytūl tamwīl, the prevailing regulations do not grant BMT authority to manage ISF, including zakat and cash waqf. However, in practice, BMT still plays a role in ISF management as a representative of Zakat Management Institutions (LAZ) and nazir for waqf. Zakat management is carried out in collaboration with LAZIZMU and LAZ Timoho Sejahtera, while cash waqf management involves partnerships with Islamic Financial Institutions as Waqf Recipients (LKS-PWU). Supervision of ISF management in BMT is conducted by the Sharia Supervisory Board (DPS), which provides general guidelines based on sharia principles and regulations, and by the Cooperative Office through regular reporting to ensure compliance with laws. These findings highlight the practice of ISF management by BMT despite being restricted by current regulations.